2012
DOI: 10.1021/jf2039197
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of Wild Citrus Mangshanyegan (Citrus nobilis Lauriro) Peel Oil

Abstract: Volatiles of a wild mandarin, Mangshanyegan (Citrus nobilis Lauriro), were characterized by GC-MS, and their aroma active compounds were identified by aroma extract dilution analysis (AEDA) and gas chromatography-olfactometry (GC-O). The volatile profile of Mangshanyegan was compared with those of other four citrus species, Kaopan pummelo (Citrus grandis), Eureka lemon (Citrus limon), Huangyanbendizao tangerine (Citrus reticulata), and Seike navel orange (Citrus sinensis). Monoterpene hydrocarbons predominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 50 publications
11
114
1
Order By: Relevance
“…Violet/woody/fruity odors were lower in GCDG than in LYJG because the total MF values of trans-β-ionone, α-ionone, and hexyl butanoate were low. Considering that the characteristic plant aroma should arise from a mixture of several aroma-active compounds (Liu et al, 2012), the less elegant and sweet aroma impression of GCDG might be due to the total MF values of aroma-active compounds which contributed to herbal and violet/ woody/fruity odors. Linalool and its oxides had not only high content, but also high MF values in GCDG.…”
Section: Discussionmentioning
confidence: 99%
“…Violet/woody/fruity odors were lower in GCDG than in LYJG because the total MF values of trans-β-ionone, α-ionone, and hexyl butanoate were low. Considering that the characteristic plant aroma should arise from a mixture of several aroma-active compounds (Liu et al, 2012), the less elegant and sweet aroma impression of GCDG might be due to the total MF values of aroma-active compounds which contributed to herbal and violet/ woody/fruity odors. Linalool and its oxides had not only high content, but also high MF values in GCDG.…”
Section: Discussionmentioning
confidence: 99%
“…The sample preparation and the volatile extraction by solvent MTBE were conducted according to Liu et al [5]. Three independent biological replicates were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Just like in other genotypes of Citrus and its relatives, monoterpenoids and sesquiterpenoids play dominant roles in the volatile profile of Mangshanyegan peel oil. Additionally, acids, alcohols, aldehydes, esters, an alkane, an indole, and a diterpene were all identified [5]. Thus, Mangshanyegan is not only a promising and precious resource for the essential oil industry, but also a desirable object for researches regarding mechanisms of aroma production.…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals contributed to the majority of the total OAVs of the EOs, which was consistent with previous studies that D-limonene, β-myrcene, linalool, octanal, citronellal, nonanal, linalool oxide, and nootkatone were the major contributors to the aroma of citrus oils. 12,17,33 Studies have shown that an overall aromatic profile could be significantly changed by some changes of volatiles in small concentrations but with very low odor thresholds. 17,39 For instance, many oxygenated compounds have been recognized with high OAVs that may have significant impacts on overall flavors.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…17,39 For instance, many oxygenated compounds have been recognized with high OAVs that may have significant impacts on overall flavors. 9,12 To explore the potent volatiles responsible for the aroma changes, the EOs were further compared by the OAVs of their inherent volatiles by cluster analysis, which showed the existence of five principal clusters according to the OAV changes (Table 4 and Figure 3). Cluster 1 represented the volatiles that did not exist in the fresh EO (sample 1) but had been generated with significantly high OAVs in the sunlightexposed EOs (samples 2 and 3) and heated EOs (sample 5), which contributed to the oily and ripened notes.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%